2015
DOI: 10.1152/jn.00667.2014
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic enhancement induced by gintonin via lysophosphatidic acid receptor activation in central synapses

Abstract: Park H, Kim S, Rhee J, Kim HJ, Han JS, Nah SY, Chung C. Synaptic enhancement induced by gintonin via lysophosphatidic acid receptor activation in central synapses. J Neurophysiol 113: 1493-1500, 2015. First published December 10, 2014 doi:10.1152/jn.00667.2014 is one of the well-characterized, ubiquitous phospholipid molecules. LPA exerts its effect by activating G protein-coupled receptors known as LPA receptors (LPARs). So far, LPAR signaling has been critically implicated during early development stages, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…For playing their role in metabolic and homeostatic functions of the nervous system, astrocytes contain gliotransmitters, which are used for intercellular communication between astrocytes and neurons [11]. In previous reports, we have shown gintonin enhanced synaptic transmission by stimulating the release of glutamate in hippocampal slices [9]. Gintonin also enhances NMDA receptor channel currents [14].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For playing their role in metabolic and homeostatic functions of the nervous system, astrocytes contain gliotransmitters, which are used for intercellular communication between astrocytes and neurons [11]. In previous reports, we have shown gintonin enhanced synaptic transmission by stimulating the release of glutamate in hippocampal slices [9]. Gintonin also enhances NMDA receptor channel currents [14].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, gintonin-mediated LPA receptor activation, and the following [Ca 2+ ] i transients, are linked to the regulation of intracellular Ca 2+ -dependent ion channels and receptors [8]. Further studies showed that gintonin mediated-[Ca 2+ ] i transients are also coupled to interneuron communication [9]. Although previous reports raise the possibility that gintonin-mediated [Ca 2+ ] i transients via LPA receptors play a key role in intra-and inter-neuronal communication, it has not been demonstrated that gintonin-mediated activation of G protein-coupled LPA receptors in primary astrocytes is coupled to the regulation of gliotransmitter release.…”
Section: Introductionmentioning
confidence: 96%
“…S4). Moreover, gintonin increases hippocampal synaptic transmission via LPA1 receptor [33]. In addition, in vitro gintonin treatment of hippocampal neural progenitor cells may have stimulated their proliferation by increasing the number of LPA1 receptors in hippocampal NPCs due to enhanced LPA1 receptor and brain-derived neurotrophic factor expression [23,34].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we showed that ginseng contains a novel G protein-coupled lysophosphatidic acid (LPA) receptor ligand, gintonin ( Hwang et al, 2012a ; Pyo et al, 2011 ). Gintonin enhanced synaptic transmission in hippocampal slices through LPA receptor signaling pathways ( Park et al, 2015 ). We showed that gintonin is the active component of ginseng to attenuate AD-related neuropathies via activation of non-amyloidogenic pathways; gintonin significantly improved Aβ-induced cognitive dysfunctions in mice.…”
Section: Introductionmentioning
confidence: 99%